Optimization of One-Step Block Method for Solving Second-Order Fuzzy Initial Value Problems. (29th April 2021) - Al-Refai, Safa; Syam, Muhammed I.; Al-Refai, Mohammed
Abstract : In this article, we present a one-step hybrid block method for approximating the solutions of second-order fuzzy initial value problems. We prove the stability and convergence results of the method and present several examples to illustrate the efficiency and accuracy of the proposed method. The numerical results are compared with the existing ones in the literature.